Interdisciplinary communication in orthopedic surgical planning - Kostevšek, Urška; Drstvensek, Igor; Balič, Jože; Moličnik, Andrej; Vogrin, Matjaž; Stević, Snezana; Brajlih, Tomaz (Journal of Production Engineering, 2018)
The paper describes a process of 3D planning of replacement of an acetabular component on a case of a defect with a huge bone loss estimated at level IIIa according to Paprosky. The planning was based on CT scans of the affected area and performed in interdisciplinary cooperation among surgeons and mechanical engineers. This cooperation combined surgical experiences and knowledge of surgeons with knowledge of engineers in using 3D design tools and mechanical calculation. The cooperation resulted in a virtual 3D plan and 3D printed communication models that enabled flawless communication among the team members. This lead to a definition of optimal hip parameters (centre of rotation, inclination and version angles) in a virtual computer space. To transfer the virtually planned parameters and shapes into a real environment surgical equipment were custom made for the particular patient. These were surgical guides used to help the surgeon resect the femoral neck and to hold and guide the reamer while reshaping the acetabular cave. This way the centre of rotation, inclination and version angles were precisely transferred from a virtual computer space into the patient’s hip. The implementation of the described procedure required some changes in the surgical process. To that purpose special documentation has been prepared that enables the surgeon to approve the surgical plan. Additionally, a user’s guide was written that lists and describes all patient specific instruments and their use to enable a flawless surgical process.